2019
DOI: 10.1183/13993003.00913-2019
|View full text |Cite
|
Sign up to set email alerts
|

Early life exposure to air pollution and incidence of childhood asthma, allergic rhinitis and eczema

Abstract: RationaleThere is growing evidence that air pollution may contribute to the development of childhood asthma and other allergic diseases. In this follow-up of the Toronto Child Health Evaluation Questionnaire (T-CHEQ) study, we examined associations between early life exposures to air pollution and incidence of asthma, allergic rhinitis and eczema from birth through adolescence.Methods1286 T-CHEQ participants were followed from birth until outcome (March 31, 2016) or loss to follow-up, with a mean of 17 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 46 publications
(61 reference statements)
2
82
0
1
Order By: Relevance
“…This phenomenon is particularly evident in children, as they are more susceptible to NO 2 -induced lung damage. Hence, viral infection becomes more common after exposure to NO 2 ( Zhu et al, 2020 ), Furthermore, NO 2 is associated with other several health effects such as elevated risks for asthma, allergic rhinitis and eczema in children ( To et al, 2020 ), increase of outpatient visits and hospitalizations due to bronchitis and asthma exacerbation ( Bahrami Asl et al, 2018 ; Kowalska et al, 2020 ), increase of chronic obstructive pulmonary disease (COPD) ( Ghanbari Ghozikali et al, 2016 ; Pfeffer et al, 2019 ) and increase of pulmonary heart disease - related mortality ( Chen et al, 2019 ).…”
Section: Nitrogen Dioxide (No2) and Covid-19mentioning
confidence: 99%
“…This phenomenon is particularly evident in children, as they are more susceptible to NO 2 -induced lung damage. Hence, viral infection becomes more common after exposure to NO 2 ( Zhu et al, 2020 ), Furthermore, NO 2 is associated with other several health effects such as elevated risks for asthma, allergic rhinitis and eczema in children ( To et al, 2020 ), increase of outpatient visits and hospitalizations due to bronchitis and asthma exacerbation ( Bahrami Asl et al, 2018 ; Kowalska et al, 2020 ), increase of chronic obstructive pulmonary disease (COPD) ( Ghanbari Ghozikali et al, 2016 ; Pfeffer et al, 2019 ) and increase of pulmonary heart disease - related mortality ( Chen et al, 2019 ).…”
Section: Nitrogen Dioxide (No2) and Covid-19mentioning
confidence: 99%
“…2 In particular, an increase in air pollutants in the environment has been found to be associated with increased incidence of allergic respiratory diseases 15 ; with one study in children demonstrating that exposure to oxidizing pollutants in the air leads to a higher risk of developing AR in these children. 16 There is evidence that exposure to the particulate matter (PM2.5) in the environment may increase the degree of DNA methylation in the body. 17 Furthermore, environmental factors can also lead to phenotypic genetic changes that promote the increase in allergic diseases.…”
Section: Environmental Fac Tor Smentioning
confidence: 99%
“…A birth cohort study in Canada reported that ozone exposure at birth was associated with the onset of asthma and allergic rhinitis during a follow-up at age 17. 36 In France, a higher annual outdoor concentration of ozone was associated with increased total IgE levels. 37 A study estimated that 7-day exposure to ozone was associated with significant increase in physician visits for atopic dermatitis, contact dermatitis and urticaria.…”
Section: Many Of the Factors That Have Been Implicated In Allergic DImentioning
confidence: 99%